Dampak Implementasi Risiko Kredit, Risiko Likuiditas, Modal Bank, Ukuran Bank Terhadap Profitabilitas - Keisha Alvera Herwina Sadie; M. Hendri Yan Nyale (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to assess the impact of credit risk, liquidity risk, bank capital, and bank size on the profitability of banking companies listed on the Indonesia Stock Exchange during the period 2021-2023. Employing a quantitative method, the study explores correlations among variables using secondary data from annual reports, utilizing purposive sampling. Multiple linear regression analysis reveals that credit risk (NPL), bank capital (CAR), and bank size (Ln Assets) negatively influence profitability (ROA), whereas liquidity risk (LDR) has a positive impact on profitability. The study suggests enhancements in risk management and capital augmentation to bolster bank profitability.